Early attainment of 20-hydroxyecdysone threshold shapes mosquito sexual dimorphism in developmental timing - Meichun Zhang; Han Wen; Qiang Sun; Dongjing Zhang; Yongjun Li; Andrew Xi; Xiaoying Zheng; Yu Wu; Jun Cao; Jeremy Bouyer; Zhiyong Xi (Nature Communications)
Abstract In holometabolous insects, critical weight (CW) attainment triggers pupation and metamorphosis, but its mechanism remains unclear in non-model organisms like mosquitoes. Here, we investigate the role of 20-hydroxyecdysone (20E) in CW assessment and pupation timing in Aedes albopictus and Ae. aegypti, vectors of arboviruses including dengue and Zika. Our results show that the attainment of CW is contingent upon surpassing a critical 20E threshold, which results in entrance into a constant 22 h interval and the subsequent 20E pulse responsible for larval-pupal ecdysis. Sexual dimorphism in pupation time arises from higher basal 20E levels in males, enabling earlier CW attainment. Administering 20E at 50% of L3/L4 molt, when most of males but not females pass the pulse, results in female-specific lethality. These findings highlight the pivotal role of 20E thresholds in CW, pupation timing, and sexual dimorphism, suggesting that manipulating 20E levels can skew populations male, offering a potential mosquito sex separation strategy.